2019
DOI: 10.1088/1361-6463/ab2859
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of high-quality C-face and Si-face 3C-SiC(1 1 1) grown on off-oriented 4H-SiC substrates

Abstract: We present a comparative study of the C-face and Si-face of 3C-SiC(111) grown on off-oriented 4H-SiC substrates by the sublimation epitaxy. By the lateral enlargement method, we demonstrate that the high-quality bulk-like C-face 3C-SiC with thickness of ~1 mm can be grown over a large single domain without double positioning boundaries (DPBs), which are known to have a strongly negative impact on the electronic properties of the material. Moreover, the C-face sample exhibits a smoother surface with one unit ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This indicates that using hexagonal SiC substrates with even higher off-cut angles could be the right direction for further research, even though the growth on such substrates will require growing much thicker layers to obtain a full coverage with 3C-SiC. Therefore, a comparative study of the 3C-SiC(111) grown on the (0001)/Si-face and (000-1)/C-face on 4 degrees off-oriented 4H-SiC research size (7 × 7 mm 2 ) substrates was conducted [ 68 ]. Even though the 3C-SiC polytype is more stable on the (0001)/Si-face, it was shown that smoother surfaces of 3C-SiC could be obtained on the C-face.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that using hexagonal SiC substrates with even higher off-cut angles could be the right direction for further research, even though the growth on such substrates will require growing much thicker layers to obtain a full coverage with 3C-SiC. Therefore, a comparative study of the 3C-SiC(111) grown on the (0001)/Si-face and (000-1)/C-face on 4 degrees off-oriented 4H-SiC research size (7 × 7 mm 2 ) substrates was conducted [ 68 ]. Even though the 3C-SiC polytype is more stable on the (0001)/Si-face, it was shown that smoother surfaces of 3C-SiC could be obtained on the C-face.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical histogram of step heights (Figure b) on the C‐face 3C‐SiC confirms that most of the steps are distributed around 0.75 nm height, which corresponds to three Si‐C bilayers or one‐3C‐SiC unit cell. In addition, the terraces/steps are straight and have length in tens or even hundreds of micrometers, indicating that the 3C‐SiC was grown on off‐axis 4H‐SiC substrate by a step‐flow growth mode without step‐bunching or DPB formation …”
Section: Resultsmentioning
confidence: 99%
“…Most recently, we have demonstrated that single-domain C-face 3C-SiC single crystal can be grown on off-axis 4H-SiC substrates and its crystalline quality has been significantly improved. [29] This allows DOI: 10.1002/pssb.201900718 Graphene layers grown on the C-face SiC exhibit quite different structural and electronic properties compared with those grown on the Si-face SiC. Herein, the growth and structural properties of graphene on the off-axis C-face 3C-SiC(1 1 1) are studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These four modes have been observed for various SiC polytypes [97]. By comparing peak positions of the measured spectrum to standard spectrums of SiC, one can determine the SiC polytypes [98].…”
Section: Raman Spectroscopymentioning
confidence: 87%